Long-term maintenance treatment of ulcerative colitis in eastern India: a 15-year follow-up. (July 2018) - Ray, Gautam
Clinical data of 65 histologically documented ulcerative colitis patients from January 2001 to December 2013 were prospectively recorded till June 2017 and analysed to determine the outcome of long-term maintenance treatment. Drugs used were 5-aminosalicylates, steroids and azathioprine. Primary outcome measure was relapse. Though 73.8% patients relapsed, most occurred within the first five years with mild to moderate severity and were easily controlled with the same medicines. None had progressive disease; drug discontinuation was possible in six cases. Side effects of drugs were negligible. Rates of surgery, colon cancer, complications and disease-related death were very low. Longer disease duration, azathioprine discontinuation and 5-aminosalicylate use in dose < 2.4 g/d were positively associated with relapses. Biologics were not used in any patient. We conclude that long-term effective use of low-cost drugs in India may obviate the need for newer more expensive drugs.